Market microstructure confronting many viewpoints - Abergel, Frédéric (Wiley, 2012)
The latest cutting-edge research on market microstructure Based on the December 2010 conference on market microstructure, organized with the help of the Institut Louis Bachelier, this guide brings together the leading thinkers to discuss this important field of modern finance. It provides readers with vital insight on the origin of the well-known anomalous "stylized facts" in financial prices series, namely heavy tails, volatility, and clustering, and illustrates their impact on the organization of markets, execution costs, price impact, organization liquidity in electronic markets, and other.
Includes bibliographical references and index. - Print version record
Keywords: Securities; Securities -- Prices; Stock exchanges; Microfinance; Valeurs mobilières; Prix; Bourse; stock exchanges; BUSINESS & ECONOMICS; Investments & Securities; General; Securities; Prices